The effects flooding on house prices: two case studies in Malaysia / Abdul Mutalib bin Mohammad Beksin. - Mohammad Beksin, Abdul Mutalib (2011)
Flooding of residential property is a real and growing phenomenon in the Malaysia and is causing short and long-term detriment of various kinds to its victims. The issue of potential decrease in value of those properties which are located on the floodplain, though much discussed in the media, has received scant attention in the Malaysian research literature. An extensive literature survey of Anglo-Saxon and US origin has revealed a need for methodological innovation in the field of temporal impact of flooding and the inadequacy of the current paradigms for inclusion of insurance into flood modelling. The main thrust of this research is to determine whether flooding has any effect on housing prices in Malaysia. The ancillary objectives of this study are limited to a search for evidence that expected annual flood damages borne by flood plain activities are or are not capitalized into the fair market value of floodplain properties in Malaysia. Addressing this question is more involved than just comparing the actual price of a floodplain property to a hypothetical, otherwise identical, non-floodplain property. This study defines this difference as the discount for floodplain location. The discount for floodplain location, however, does not necessarily equate to discount for primary flood damages. The location discount represents the net effect of all attributes, positive and negative alike, associated with floodplain location which affects property value. Examples of positive attributes are access to recreational boating and river views. Negative attributes include clean-up costs and loss of income during a flood. Hedonic price models are used to empirically measure a discount due to primary flood damages, separate from the discount for floodplain location. Hedonic price models describe the contribution of a property attribute to the overall price. The models are empirically assessed with multi-variety regression models where sale price is the dependent variable and the property attributes are the independent variables. This study reviewed existing academic literature on hedonic price models of the floodplain real estate market. In addition, two hedonic price model cases were studied to answer some of the questions raised in the literature review. The case studies used price data on Damansara and Dungun. The output from this study makes a contribution to the understanding of the impact of flooding on house prices, allowing for better valuation advice. Empirical findings are that the understandable concerns of residential property owners at risk of flooding regarding long term loss of property value are largely unfounded. Price discounts are observed for some recently flooded areas but they are temporary. The output from the study also makes a methodological contribution in extending concepts relating to the relationship between flooding, insurance and house prices. This development is anticipated to facilitate refinement and updating of the empirical findings with reduced effort in the light of future events